(untitled) (Lex localis - Journal of Local Self-Government, 2025)
The main objective of this study was to identify the sociodemographic, economic, and institutional factors that influence student performance on the Saber Pro tests in Colombia. The research was conducted using a quantitative, descriptive, and correlational approach with a non-experimental design. The Ordinary Least Squares (OLS) regression technique was applied to a database comprising 139,288 students who took the tests during the 2023-1 and 2024-1 periods. The variables analyzed included gender, socioeconomic status, age, educational modality (face-to-face or virtual), parents’ educational level, internet access, method of preparation before the test, form of payment for studies, and number of hours worked. Among the most relevant findings is that men obtain, on average, better results than women, although the difference is slight. Socioeconomic status shows a positive relationship with scores: students in strata 4, 5, and 6 obtain significantly higher scores. Likewise, students enrolled in face-to-face programs perform better than those studying in distance learning programs. Internet access and the fact that parents have postgraduate education are also associated with better performance. In terms of preparation methods, those who took formal courses obtained better results than those who did not prepare or only reviewed on their own. Based on these results, it can be concluded that there are structural inequalities that affect academic performance. It is recommended that public policies be implemented that focus on reducing gender and socioeconomic gaps starting in basic education, expanding access to technological resources, and strengthening educational quality in public institutions. Finally, it is suggested that longitudinal studies be conducted to observe the evolution of student performance throughout the educational process.